Nickel oxide film saturable absorber for mode-locking operation at 1.55-micron region - Harun, Sulaiman Wadi; Nawi, B.M.; Latiff, Anas Abdul (World Scientific Publishing, 2018)
The generation of mode-locking pulse train in Erbium-doped fiber laser (EDFL) cavity was demonstrated using Nickel Oxide (NiO) saturable absorber (SA). The NiO compound synthesized via sonochemical method was embedded into poly ethylene oxide (PEO) film through solution casting technique to fabricate the SA film device. A small piece of the SA film was sandwiched between two ferrules in the EDFL cavity. By adding 180m single mode fiber (SMF) in the ring cavity, a stable mode-locking pulse train operating at 1558nm with a repetition rate of 1.1MHz was achieved. At 197.5mW pump power, the proposed mode-locked EDFL has output power and pulse energy of 3.35mW and 3.36nJ, respectively. This study may well be the first demonstration of mode-locked EDFL using NiO-based SA. The result indicates that NiO is the promising material for ultrafast photonic applications.